Parasites destabilize host populations by shifting stage‐structured interactions. Issue 2 (7th March 2016) - Hite, Jessica L.; Penczykowski, Rachel M.; Shocket, Marta S.; Strauss, Alexander T.; Orlando, Paul A.; Duffy, Meghan A.; Cáceres, Carla E.; Hall, Spencer R.
Abstract: Should parasites stabilize or destabilize consumer–resource dynamics? Recent theory suggests that parasite‐enhanced mortality may confer underappreciated stability to their hosts. We tested this hypothesis using disease in zooplankton. Across both natural and experimental epidemics, bigger epidemics correlated with larger—not smaller—host fluctuations. Thus, we tested two mechanistic hypotheses to explain destabilization or apparent destabilization by parasites. First, enrichment could, in principle, simultaneously enhance both instability and disease prevalence. In natural epidemics, destabilization was correlated with enrichment (indexed by total phosphorous). However, an in situ (lake enclosure) experiment did not support these links. Instead, field and experimental results point to a novel destabilizing mechanism involving host stage structure. Epidemics pushed hosts from relatively more stable host dynamics with less‐synchronized juveniles and adults to less stable dynamics with more‐synchronized juveniles and adults. Our results demonstrate how links between host stage structure and disease can shape host/consumer–resource stability.